Routine clinical heart examinations using SQUID magnetocardiography at University of Tsukuba Hospital. (6th October 2017) - Inaba, T; Nakazawa, Y; Yoshida, K; Kato, Y; Hattori, A; Kimura, T; Hoshi, T; Ishizu, T; Seo, Y; Sato, A; Sekiguchi, Y; Nogami, A; et al.
Abstract: A 64-channel Nb-based DC-SQUID magnetocardiography (MCG) system was installed at the University of Tsukuba Hospital (UTH) in March 2007 after obtaining Japanese pharmaceutical approval and insurance reimbursement approval. In the period between 2008 and 2016, the total number of patients was 10 085. The heart diseases diagnosed in fetuses as well as adults are mainly atrial arrhythmia, abnormal repolarization, ventricular arrhythmia, and fetal arrhythmia. In most cases of insufficient diagnostic accuracy with electrocardiography, SQUID MCG precisely revealed these heart diseases as an abnormal electrical current distribution. Based on success in routine examinations, SQUID MCG is now an indispensable clinical instrument with diagnostic software tuned up during routine use at UTH.